High resolution AFM studies of irradiated mica—following the traces of swift heavy ions under grazing incidence. (18th June 2018) - Gruber, Elisabeth; Bergen, Lorenz; Salou, Pierre; Lattouf, Elie; Grygiel, Clara; Wang, Yuyu; Benyagoub, Abdenacer; Levavasseur, Delphine; Rangama, Jimmy; Lebius, Henning; Ban-d'Etat, Brigitte; Schleberger, Marika; et al.
Abstract: High resolution AFM imaging of swift heavy ion irradiated muscovite mica under grazing incidence provides detailed insight into the created nanostructure features. Swift heavy ions under grazing incidence form a complex track structure along the surface, which consists of a double track of nanohillocks at the impact site accompanied by a single, several 100 nm long protrusion. Detailed track studies by varying the irradiation parameters, i.e. the angle of incidence (0.2°–2°) and the kinetic energy of the impinging ions (23, 55, 75, 95 MeV) are presented. Moreover, the track formation in dependence of the sample temperature (between room temperature and 600 °C) and of the chemical composition (muscovite mica and fluorphlogopite mica) is studied.